EFEKTIVITAS SATUAN PEMERIKSAAN INTERNAL PADA UNIT BADAN LAYANAN UMUM - Adhini Wijayanti; Harti Budi Yanti; Ice Nasyrah Noor (Media Riset Akuntansi, Auditing & Informasi, 2020)
The purpose of this study is to examine the factors that influence the effectiveness of Internal Audit (Internal Audit Unit) in the Public Service Agency unit of the Ministry of Transportation office, Jakarta, including Internal Auditor Competency, Objectivity of Internal Auditor, Management Support and Work Experience. There are 3 (three) independent variables that affect the effectiveness of Internal Audit as the dependent variable, namely Internal Auditor Competency, Objectivity of Internal Auditor, Management Support with Internal Auditor Work Experience (Internal Audit Unit) as a moderating variable. The population in this study was 110 internal auditors working in the Internal Audit Unit of the Public Service Agency's Office of the Ministry of Transportation. This study uses primary data in the form of questionnaires, 100 questionnaires can be processed using the method of Multiple Linear Regression. Based on the analysis of the independent variables significantly positive effect on the dependent variable with Work Experience as a moderating.